(untitled) (Journal of Health, Population and Nutrition, 2013)
The study examined the secular trends in growth of preschool children from rural Maharashtra, India, during 1985-2001. Anthropometric data collected on preschool (<6 years old) children during 2001 (n=1,171) and 1985 (n=979) from the same villages were compared. Decadal change increased with age and was marginally higher in boys than girls. It was the lowest among infants (-0.1 to 0.1 kg and 0.4 to 0.7 cm in both sexes) and the highest among boys of 4+ years (1.3 kg and 2.9 cm) and girls of 5+ years (1.2 kg and 2.1 cm). Increase in weight was higher (10-15%) compared to that in height (3-5%) and, consequently, reduction in the prevalence of wasting was marked (around 68% in boys and 48% in girls) than that in stunting (42% in boys and 27% in girls) among these children. The improvement was higher in boys than in girls. Negligible secular changes in younger children indicate the need for creating health and nutritional awareness among rural mothers while relatively higher improvement in weight than height among older children warns the future possibility of childhood adiposity even among rural populations. DOI: http://dx.doi.org/10.3329/jhpn.v30i4.13325 J HEALTH POPUL NUTR 2012 Dec;30(4):420-430